Indole-3-acetic acid and chenodeoxycholic acid attenuate TLR4/NF-κB signaling and endoplasmic reticulum stress in valproic acid-induced neurotoxicity - Sarawi, Wedad S.; Alhusaini, Ahlam M.; Barwaished, Ghada S.; Altamimi, Myasah M.; Hasan, Iman H.; Aljarboa, Amjad S.; Algarzae, Norah K.; Bakheet, Saleh A.; Alhabardi, Samiah A.; Ahmad, Sheikh F. (Frontiers in Pharmacology, 2025)
Valproic acid (VA) is a commonly prescribed medication for epilepsy and other neurological conditions. Although effective, VA use can lead to neurotoxicity, especially with chronic use. This study aimed to investigate the potential neuroprotective properties of indole-3-acetic acid (IAA) and chenodeoxycholic acid (CDCA) in an animal model of VA-induced brain injury. Rats received intraperitoneal injections of VA at a dose of 500 mg/kg/day for 3 weeks. Concurrently, they were orally treated with IAA (40 mg/kg/day) and/or CDCA (90 mg/kg/day). The results showed significantly increased oxidative stress and inflammation markers in the VA-exposed group indicated by the reduced levels of glutathione (GSH, P < 0.0001) and superoxide dismutase (SOD, P < 0.01) and the elevated inflammatory cytokines Interleukin-6 (IL-6, P < 0.0001) and tumor necrosis factor-alpha (TNFα, P < 0.01). VA also induced nuclear factor kappa B (NF-κB, P < 0.01), toll-like receptor 4 (TLR4, P < 0.05), and endoplasmic reticulum (ER) stress markers, as evidenced by increased immunoreactivity of GRP78 (glucose-regulated protein 78, P < 0.0001), transcription factor 6 (ATF-6, P < 0.05) and CHOP (C/EBP homologous protein, P < 0.0001). Treatment with IAA or CDCA attenuated VA-induced neurotoxicity, to a variable extent, by improving oxidative, inflammatory, and ER stress markers. This study demonstrates that IAA and CDCA exert protective effects against VA-induced neurotoxicity by mitigating oxidative stress, inflammation, and ER stress. Further investigations are recommended to validate these findings in other neurotoxicity models.